Protective Role of Quercetin Against Rotenone- Induced Hepato and Nephrotoxicity in Swiss Albino Mice - Jain, Juli; Hasan, Whidul; Biswas, Pronit; Singh Yadav, Rajesh; Jat, Deepali (International Journal of Human Anatomy, 2021)
Rotenone is well known environmental neurotoxin used to induce Parkinson’s disease (PD) model. Numerous studies are investigated its toxicity on the brain but few studies are available that examined its toxicity on the liver and kidney. Therefore, the main aim of the present work was to explore the toxicity of rotenone on the liver and kidney and its protection through quercetin. Administration of rotenone orally at the dose of (5mg/kg b.w daily for 60 days) caused a significant increase in the levels of liver function and renal function biomarkers as compared to controls. A significant increase in the level of lipid peroxidation, nitric oxide, and decrease in the levels of reduced glutathione, reduction in the activities of catalase and superoxide dismutase were observed in the liver and kidney as compared to control. The histopathological and SEM study in rotenone-treated mice showed alteration and signs of inflammation in the liver and kidney. While co-treatment of quercetin orally (30 mg/kg b.w for 60 days) together with rotenone, reversed the above parameters. In conclusion, rotenone significantly damages the liver and kidney, and the administration of quercetin along with rotenone shown a protective role. This study provides a new insight into where rotenone-induced liver and kidney dysfunction could be successfully protected by quercetin.
Keywords: Rotenone; liver and kidney; pesticide; quercetin